The Study of Geometry in Elementary Mathematics Textbooks in Finland, Singapore, and Taiwan - Der-Ching Yang (JME (Journal of Mathematics Education), 2020)
This study examined the differences in the presentation of geometry concepts andcharacteristics of geometry questions among elementary mathematics textbooks inFinland, Singapore, and Taiwan. Horizontal and vertical analysis methods were used tocollect and analyze the data. A popular Mathematics textbook from a dominant publisherin each country was selected: Laskutaito from Finland, My Pals are Here! Maths fromSingapore, and Kang Hsuan from Taiwan. The results indicated differences in thepresentation of geometry concepts among the three textbooks series. In addition, thequestions in these textbooks were determined to demonstrate different characteristics.Moreover, these findings highlight the importance of cross-national textbook comparisonto enhance the understanding of differences in learning opportunities across differentcountries.